Secondary metabolites produced by marine bacterirum micromonospora sp. G019 - Quyen, Vu Thi; Hieu, Tran Van; Vinh, Le Cong; Mai Huong, Doan Thi; Hong Minh, Le Thi; Murphy, Brian; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2015)
Nine compounds were isolated and characterized from the culture broth of the marine bacteria Micromonospora sp.G019 strain, which was isolated from sediment collecting at Ha Long Bay. Their structures were determined by spectroscopic analysis including MS and 2D NMR, as well as by comparison with reported data in the literature